Rolling tachyon and the phase space of open string field theory - Minjae Cho; Ben Mazel; Xi Yin (Journal of High Energy Physics)
Abstract We construct the symplectic form on the covariant phase space of the open string field theory on a ZZ-brane in c = 1 string theory, and determine the energy of the rolling tachyon solution, confirming Sen’s earlier proposal based on boundary conformal field theory and closed string considerations.